Social and Economic Aspects of Sustainable Product Development in the Textile and Clothing Industry - Kowalski, Mateusz; Salerno-Kochan, Renata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article analyses the key problems facing the textile and clothing industry, including social and economic aspects of its functioning, and puts forward steps that could be taken to bring the industry closer to sustainable development. The issues discussed include outsourcing of the clothing and textiles production, salaries that can be 50% below a living wage, and fast fashion, which endangers the sustainable development approach to the production and consumption of textile products. The paper provides examples of initiatives aimed at achieving balance in areas including multilateral agreements, independent initiatives among clothing companies to improve pay conditions, respect for employee rights and ensuring safe working conditions, and also the popularisation of slow fashion movement, a response to the dominant phenomenon of consumerism.